Lipid signalling in health and disease. (28th November 2013) - Corda, Daniela; De Matteis, Maria Antonietta
<x xml:space="preserve">Abstract</x> This series of reviews is based on the FEBS Advanced Course on 'Lipid Signaling and Cancer' (4–10 October 2012, Vico Equense, Italy). The course encompassed the relationships between studies of basic and more translational aspects on the prevalence of altered lipid metabolism in different cancer types with a particular focus on phosphoinositides and sphingolipids. The reviews highlight both the basic aspects of these lipid classes and their roles in cancer development, and their potential as drug targets in cancer treatment.<boxed-text content-type="graphic" id="febs12604-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>